PENGARUH LATIHAN AKURASI TENDANGAN PENALTI DENGAN ALAT BANTU BAN, BOLA, BOTOL GANTUNG TERHADAP AKURASI TENDANGAN PENALTI PADA PEMAIN USIA 14-15 TAHUN SSB DJARUM KUDUS TAHUN 2021 - Knang Wibisono Aji Pamungkas; Wahadi Wahadi (Universitas Negeri Semarang, 2022)
This type of research is experimental research. The sample of this study amounted to 28 people. The independent variable is training with balls, tires, bottles, and the dependent variable is the soccer shooting penalty of SSB Djarum players. From the results of the research, the accuracy of shooting penalty scores showed that before being given training using tools, the shooting penalty scores obtained by 10 or 35.7% of players were 1, 14 or 50% of players got a score of 2, and 4 or 14.3% of players got a score 3. Based on the results on the accuracy of the shooting penalty scores obtained by players, it shows that the shooting penalty scores obtained by 1 or 3.6% of players are 2.14 or 50% of players get a score of 3, and 13 or 46.4% of players get a score of 4.96.43 % or 27 samples experienced an increase in shooting penalty scores and 3.57% or 1 player did not experience a decrease or increase in results, while there was not 1 player who experienced a decrease in results. The conclusion of this study is that the accuracy of soccer penalty shooting can be improved by applying accuracy exercises using training tools in the form of tires, balls, and bottles that are hung on the goal.